Mozart's Da Ponte operas : the marriage of Figaro, Don Giovanni, Così fan tutte - Da Ponte, Lorenzo, 1749-1838 (Opera classics library., 2007)
OPERA CLASSICS LIBRARY addresses one of the most extraordinary collaborations in the history of opera: Mozart and Da Ponte, composer and librettist respectively for The Marriage of Figaro, Don Giovanni and Così fan tutte. The text includes biographical profiles of Mozart and Da Ponte, and for each opera features the Principal Characters, Brief Story Synopsis, Story Narrative with Music Highlight Examples, an insightful and in depth Commentary and Analysis, and a complete, newly translated Libretto, with Italian/English translation side-by-side, and with music examples.